Pregnancy and Cardiomyopathy After Anthracyclines in Childhood - Thompson, Kara Annette (Frontiers in Cardiovascular Medicine, 2018)
Abstract With advances in cancer therapy, there has been a remarkable increase in survival in children diagnosed with malignancies. Many of these children are treated with anthracyclines which are well known to cause cardiotoxicity. As more childhood cancer survivors reach childbearing age, many will choose to become pregnant. At this time, the factors associated with development of cardiomyopathy after anthracycline treatment are not clearly identified. It is possible that cardiac stress could predispose to cardiac deterioration in a patient with reduced functional reserve from prior anthracycline exposure. Pregnancy is one form of cardiovascular stress. The cardiac outcomes of pregnancy in childhood cancer survivors must be considered. In view of limited data, guidelines for pregnancy planning, management, and monitoring after cardiotoxic cancer therapy have not been established. This review summarizes the limited data available on the topic of pregnancy after anthracyclines in childhood. Keyword: cardiotoxicity, pregnancy, anthracyclines, childhood, survivor